The reflection of teachers in selected Yoruba comic films:a satire and a label (2018)
Teachers are professionals who develop and nurture young individuals into responsible and productive citizens. As such, the teaching profession is a noble profession which is expected to be respected by all and sundry in the society. Teachers as role models, who are professionally trained and certified, are men and women o f integrity, commitment, contentment and discipline. However, most people today do not see them this way, especially in Nigeria. This is partly due to the acts offew culprits, which the selected comic films satirize jocularly looking at the films from the perspective of sociology of literature and partly due to the way our society has labelled them, looking at the films from the perspective o f labelling theory in sociology. Hence, the reflections o f teachers in the selected Yoruba comic films are seen, in this paper, as both a satire and a label. The connection between comedy and satire in the Yoruba society suffices for seeing the reflection as a satire. This, on the other hand, is seen as a negative label on teachers in the society, as persons labelled are to behave in line with their label: according to the labelling theory. Therefore, while it is important that literature, in which film is a genre, satirizes societal ills, it is equally important that literary artists do not blur the social image of certain people. If this would be achieved, this paper concludes that generalisation must be avoided while satirising societal ills